Effect of printing parameters and post-process on surface roughness and dimensional deviation of PLA parts fabricated by extrusion-based 3D printing - KAYNAK, YUSUF (My University, 2022)
One of the commonly used additive manufacturing methods is extrusion-based 3D printing (e.g., fused filament fabrication or FFF) that is generally required post-processing to make fabricated components ready to be used. This paper considers two major points to assess the surface enhancement of components made of polylactic acid (PLA) material. One is the role of processing parameters including layer thickness, print speed, and printing temperature on dimensional and surface quality of fabricated parts. The second one is post-processing and its parameters. Vibratory surface finishing (VSF) is used as post-processing operation, and treatment time is varied to observe its effect on the surface and dimensional variation of the fabricated parts. The effect of input variables on measured outputs is also presented by using statistical approaches including regression and analysis of variance. This study reveals that layer thickness is dominating parameter to control surface and dimensional quality of both as-printed and post-treated samples. However, printing temperature also plays a notable role on the dimensional accuracy of specimens. Considering post-processing, while it is notable, duration is the key factor determining the final surface quality of fabricated samples. The surface roughness of as-printed samples was reduced by 66% through post-processing operation.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Engineering and Technology; MÜHENDİSLİK, MEKANİK; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ENGINEERING, MECHANICAL; ENGINEERING; Engineering, Computing & Technology (ENG); Automotive Engineering; General Engineering; Engineering (miscellaneous); Mechanical Engineering; Computational Mechanics; Physical Sciences; Additive manufacturing; Material extrusion; Post-processing; Polylactic acid; Surface quality; FDM PARTS; ACCURACY; OPTIMIZATION; PREDICTION; STRENGTH; DESIGN; Additive manufacturing; Material extrusion; Post-processing; Polylactic acid; Surface quality